Urheiluseuraharrastuksen alun yhteys urheilumenestykseen yksilö- ja parilajeissa: Tarkastelussa vuosien 2018–2020 maajoukkueurheilijat. - Westman, Nathalie (2025)
Westman, N. 2025. The beginning of sports club activity in assosiation with sports success in individual and pair sports: A review to athletes of national sports team during 2018–2020. The Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, 78 pp.